Studying Chemistry at School: Overcoming Challenges Together - Khmel, Nataliya; Shpyrka, Zinoviya (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
The most important theoretical and methodological aspects of studying chemistry in general secondary education institutions have been analyzed. To gain a deeper understanding of the challenges faced by secondary education students during the study of chemistry, a diagnostic experiment was conducted. An anonymous survey was conducted among students of grades 7–9 at Lviv Secondary School No. 67 (Ukraine). The results of the diagnostic experiment revealed that the main difficulties faced by students include low interest in the subject, challenges in understanding certain concepts, laws, and theories, as well as insufficient connection to practical applications in real life. A survey showed that 65% of 9th-grade students, 55% of 8th-grade students, and 35% of 7th-grade students consider chemistry to be a more difficult subject than physics or biology. Chemistry is most often associated with interest – 55.2% and fear – 26.5%, while some students feel boredom during lessons – 9.6%. Other emotions mentioned by students included surprise, sadness, and others. Approximately 60% of students believe that chemistry is closely related to other subjects, including physics, mathematics, and biology, while approximately 40% said that there is no such relationship. 15% of students believe that chemical knowledge can be practically applied in daily life, over 60% see only partial usefulness, and 25% consider it insignificant and fail to see any practical benefit. Approximately 75% of students expressed a desire to increase the practical (experimental) component of lessons. Students' self-assessment of their level of skills and knowledge in chemistry indicated that 13% of 7th-grade students, 23% of 8th-grade students, and 5% of 9th-grade students demonstrate a low level of proficiency. A sufficient level was observed in 45%, 54%, and 5%, while an average level was reported by 35%, 20%, and 85% of the students respectively. The article provides practical recommendations for solving difficulties that often arise when studying chemistry and improving the quality of the educational process.